2021
DOI: 10.1002/pol.20210269
|View full text |Cite
|
Sign up to set email alerts
|

Crack propagation behaviors in a nanoparticle‐filled rubber studied by in situ tensile electron microscopy

Abstract: Although fracture resistance is critical for rubber materials, the fracture mechanisms are poorly understood from a microscopic perspective. In this study, a crack propagation process in rubber with silica nanoparticles, which is commonly used to enhance the mechanical properties of rubber materials, was successfully observed in situ with nanoscale resolution using transmission electron microscopy (TEM). The consecutive time-sliced TEM images clarified that the crack tip propagated along the interfaces between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 62 publications
0
7
0
Order By: Relevance
“…Specially designed TEM sample holder for real‐time observations during tensile deformation [ 26–30 ] …”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Specially designed TEM sample holder for real‐time observations during tensile deformation [ 26–30 ] …”
Section: Methodsmentioning
confidence: 99%
“…Specially designed TEM sample holder for real-time observations during tensile deformation [26][27][28][29][30] counted as part of the rubber component. The weight ratios of ZnO, [32,33] the cross-linker, and anti-aging agent to the rubber component were set to be the same in the two composite sheets.…”
Section: Preparation Of Rubber/tempo-cnf Composite Sheetsmentioning
confidence: 99%
See 2 more Smart Citations
“…An older, but comprehensive overview about different fracture mechanisms was provided by Gul [16]. Recently, Watanabe et al observed a crack in situ using transmission electron microscopy [17]. The crack progressed in a stick-slip manner by delaminating rubber from the (non-treated) silica surface.…”
Section: Introductionmentioning
confidence: 99%